PENGARUH MEDIA SPINNING WHEEL TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SD NEGERI 125 KARAMPUE KECAMATAN SINJAI UTARA KABUPATEN SINJAI - Rukayah, Rukayah; Radaiyah, Radaiyah; Jauhar, Sitti (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This study is a quantitative pre-experimental study that aims to determine the significant effect of using Spinning Wheel media on Indonesian language learning outcomes in grade V of SD Negeri 125 Karampue, North Sinjai District, Sinjai Regency. This study uses a One Group Pretest-Posttest design. The variables in this study are Spinning Wheel media (independent variable) and Indonesian language learning outcomes (dependent variable). The population in this study were all fifth grade students of SD Negeri 125 Karampue, totaling 21 students, with a sampling technique using saturated sampling. The research data were obtained using a test instrument to determine students' Indonesian language learning outcomes before and after using Spinning Wheel media. The data analysis techniques used were descriptive statistical analysis techniques and inferential statistical analysis techniques. Based on the descriptive statistical analysis, the average pretest score of 50 was in the less category while the average posttest score of 73.5 was in the good category. The data obtained were then analyzed using the Paired Sample t-Test with a significance level of 5%. From the data results obtained tcount (9.118) (>) ttable (2.08596). Thus, H₀ is rejected and H₁ is accepted, it can be concluded that the Spinning Wheel media has a significant effect on the learning outcomes of Indonesian Language at SD Negeri 125 Karampue, Sinjai Utara District, Sinjai Regency.